Light‐Induced Solid‐State Protrusion of Gold Nanowires and Their Derivatives for Sensing Applications. Issue 6 (12th January 2022) - Wang, Shuangshuang; Yao, Jiacheng; Lu, Xiaolin; Ding, Tao
Abstract: Gold nanowires (AuNWs) have been one of the key components for nanoelectronics and optoelectronic devices but the fabrication has been poorly customized for this purpose even though diverse synthetic strategies bloomed over the last decades. Here, the concept of light‐induced protrusion of AuNWs directly from solid state substrate is demonstrated, which is highly compatible for on‐chip fabrication of functional nanodevices. This is realized by irradiating the Au ion‐doped titanium dioxide (TiO2 ) films with continuous wave laser. The blue laser triggers the reduction and nucleation of Au(0) which grows vertically into AuNW bundles with diffusion‐controlled supply of Au ions within the TiO2 matrix. Thus, the morphology of the AuNWs can be tuned with irradiation time/power as well as the ion concentration, which can derive into Au nanorings (NRs) and NR stacks in 1D photonic crystal with reduced plasmon linewidth. Such light‐induced protrusion can also generate nanopillars by introducing Au seeds before irradiation. The surface‐enhanced Raman scattering performance of the AuNW bundles is excellent with fm detection limit. Such laser‐directed solid‐state growth technique is facile, versatile, cost‐effective site‐selective, ligand‐free, and wafer‐scalable, which opens up many promising applications in (bio)chemical sensing, photovoltaics, photocatalysis, plasmonic displays, and integrated nanoelectronic/optoelectronic devices. Abstract : Light‐induced protrusion of complex gold nanostructures is realized on gold (Au)‐doped titanium dioxide films, which forms bundles of Au nanowires and Au nanorings (stacks), depending on the dielectrics of surrounding medium. These complex plasmonic nanostructures bear multiple hotspots, which are promising platforms for chemical sensing and photocatalysis.